2006
DOI: 10.1127/0003-9136/2006/0167-0515
|View full text |Cite
|
Sign up to set email alerts
|

Food chain effects of sublethal ultraviolet radiation on subarctic Daphnia pulex – a field and laboratory study

Abstract: In shallow subarctic ponds Daphnia and their algal food are often exposed to solar ultraviolet radiation (UVR). It was previously demonstrated that direct exposure of Daphnia to UVR may result in sublethal damage to Daphnia's intestinal system. This led to the hypothesis that, as consequences of such exposures, Daphnia may be experiencing a situation similar to starvation. We examined, in controlled experiments, the indirect effect of UVR-treated food algae on Daphnia pulex which, themselves, were also exposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…Some metabolic and physiological effects of sub-lethal UV doses on cladoceran species have also been noted, such as decreased/increased respiration rates [73], reduced activities of digestive enzymes, and reduced residence time of algae in the gut [41]. Our study is the first to demonstrate a negative effect of sub-lethal UVB doses on the filtration rate of cladocerans.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Some metabolic and physiological effects of sub-lethal UV doses on cladoceran species have also been noted, such as decreased/increased respiration rates [73], reduced activities of digestive enzymes, and reduced residence time of algae in the gut [41]. Our study is the first to demonstrate a negative effect of sub-lethal UVB doses on the filtration rate of cladocerans.…”
Section: Discussionsupporting
confidence: 52%
“…Therefore, it is unlikely that increased UVB doses will affect zooplankton mortality rates dramatically in nature. Sub-lethal damages, on the other hand, are likely more important than lethal effects, and may affect zooplankton in more subtle ways reducing their fitness [24, 25, 41]. …”
Section: Introductionmentioning
confidence: 99%
“…Zellmer et al. (15) have shown that in D. pulex , UVR exposure can delay the onset of feeding, slow movement of algae through the gut and cause damage to the gut itself. Zellmer et al.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these protective mechanisms, elevated UVR has been shown to have deleterious effects on survival and reproduction in zooplankters such as Daphnia (10–13). These include direct effects due to DNA disruption (14), organ damage (15,16) and changes in physiology (17), as well as indirect effects such as reduced nutrition and extended exposure to suboptimal temperatures due to longer periods deeper in the water column (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…Results from Zellmer et al. (22) showed that UV irradiation damages the gut of Daphnia pulex impeding their ability to assimilate nutrients. The resulting malnourished animals had poorer survival, and although not examined in their study, may have had reduced reproductive output and offspring of lower fitness.…”
Section: Discussionmentioning
confidence: 99%